2019
DOI: 10.1089/jwh.2018.6962
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Cancer: A U.S. Population-Based Study

Abstract: Background: The incidence of pregnancy-associated cancer (PAC) is expected to increase as more women delay childbearing until later ages. However, information on frequency and incidence of PAC is scarce in the United States. Methods: We identified pregnancies among women aged 10-54 years during 2001-2013 from five U.S. health plans participating in the Cancer Research Network (CRN) and the Medication Exposure in Pregnancy Risk Evaluation Program (MEPREP). We extracted information from the health plans' adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 24 publications
2
70
1
Order By: Relevance
“…The majority of the studies were based on national registries. Five studies relied on a database covering 20% of country community hospital inpatient stays [12,13,[15][16][17], and one used data from two multicentric studies [14]. Among the registry-based studies, ten used data from a linkage between a hospital discharge registry, a maternal/birth registry and a cancer registry [2][3][4][6][7][8][9][10]25,26].…”
Section: General Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies were based on national registries. Five studies relied on a database covering 20% of country community hospital inpatient stays [12,13,[15][16][17], and one used data from two multicentric studies [14]. Among the registry-based studies, ten used data from a linkage between a hospital discharge registry, a maternal/birth registry and a cancer registry [2][3][4][6][7][8][9][10]25,26].…”
Section: General Characteristicsmentioning
confidence: 99%
“…Most of the studies on PACs reported the most frequent types of tumor [2][3][4][5]14,18,[20][21][22][23][24] (Table S1). In a Swedish study, the most common tumors were breast, melanoma and cervical cancer.…”
Section: Definition and Estimated Frequency Of Pacmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer (BC) is the most frequent female cancer worldwide, and the leading cause of cancer-related death among women [ 1 ]. It is also one of the most common types of cancer encountered during pregnancy [ 2 , 3 ]. Data regarding the global burden of disease between 1990–2017 among Romanian women of fertile age (15–49 years) reveal that although the number of BC-related deaths has decreased, the importance of BC as a cause of mortality has increased by 38.51%.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-related disease occurs in 0.2-3.8% of all breast cancer patients, comprising 1:10000 to 1:3000 pregnancies. The prevalence is much higher in pre-menopausal women, with 10-25% of breast cancers estimated to be pregnancy-associated [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%